Risks and benefits of different methods of complementery feeding (Research, Society and Development, 2021)
Introduction: The first years of a child's life are characterized by rapid growth and digestive and neuropsychomotor development, including skills such as: receiving, chewing and digesting foods other than breast milk. Objective: to understand if there are any of the different complementary feeding methods that offer greater risk or benefits for the baby's health, development and safety. Methodology: Complementary feeding AND Baby led weaning AND Infant nutrition were used. According to the Medical Subject Headings (MeSH) and Descriptors in Health Sciences (DeCS), of the three thermologies, only one, Infant Nutrition, appears in the controlled vocabulary. Among the 105 articles found, 71 from the US National Library of Medicine (PubMed) and 34 from the Virtual Health Library (VHL), 23 were present in both databases, 21 articles were read in full and 8 were eligible for the present work Results and discussion: 8 papers were analyzed for this review, of which 6 are randomized clinical trials, 1 pilot study conducted through a questionnaire and 1 study conducted through an online questionnaire. In addition to the values ​​based on the weighing of the diet, at 12 months the babies underwent a laboratory evaluation through blood collection. The values ​​for hemoglobin (g / dl) in the control group was 11.7 and in the BLISS group 11.6. Conclusion: This review did not identify significant differences between the different methods of food introduction.